blaKPC gene Detection in Clinical Isolates of Carbapenem Resistant Enterobacteriaceae in a Tertiary Care Hospital - Priyadarshini Shanmugam; Jeya Meenakshisundaram; Perumal Jayaraman (Journal of Clinical and Diagnostic Research, 2013)
Introduction: Carbapenem resistance among Enterobacteriaceae, especially in Klebsiella pneumoniae and Escherichia coli, is an emerging problem worldwide. A common mechanism of carbapenem resistance is the production of class-A, Klebsiella pneumoniae carbapenemase (KPC). Aims and Objectives: The present study focused on determining the antibiotic resistance pattern and prevalence of bla KPC gene coding for KPC in carbapenem resistant Enterobacteriaceae. Methodology: Forty six carbapenem resistant isolates belonging to the family Enterobacteriaceae were tested for antibiotic sensitivity pattern. Modified Hodge Test (MHT) and PCR for bla KPC gene detection were performed on these isolates. Of these, 22 were Klebsiella pneumoniae, 21 were Escherichia coli, 2 were Citrobacter species and 1 was Proteus mirabilis Results: Forty three (93.4%) out of the 46 isolates were resistant to Meropenem, 34 (73.9%) were resistant to Imipenem and 30 (65.2%) were resistant to both Imipenem and Meropenem. Modified Hodge Test was positive in 38 (82.6%) out of 46 isolates and blaKPC gene was detected in 31 (67.4%) isolates. bla KPC gene was detected in 28 out of the 38 MHT positive isolates.